Does Subclinical Malabsorption of Carbohydrates Prevent Colorectal Cancer? A Hypothesis - Terry Dorcen Bolin (Canadian Journal of Gastroenterology)
The incidence of colorectal cancer (CRC) is high in the western world and low in Asia and Africa. Fibre and starch are thought to be important protective factors, with a strong inverse relationship between starch consumption and CRC incidence. Whether this is true in Asia, particularly, and Africa is debatable. Because rice is the most easily absorbed of carbohydrates, a mechanism whereby there is an increased starch load in the colon in the Asian population needs to be identified. One possible cause is subclinical malabsorption. This is linked to increased mucosal permeability and low gross domestic product (GDP) per capita, which reflects poor sanitation and water supplies with increased risk for small bowel bacterial overgrowth leading to mucosal cell damage. A potential cause of the dramatic rise in CRC incidence in Japan may relate to its equally dramatic increase in GDP per capita of 600% over 50 years. This correlation appears to be stronger than with other dietary factors including fruit, vegetables and meat. Worldwide, a close correlation exists among low GDP per capita, low CRC incidence and presumed subclinical malabsorption. All these factors combine to maintain a low incidence of CRC in poorly developed countries.